2010
DOI: 10.1007/s00374-010-0457-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of alkalinity tolerance in two cucumber genotypes inoculated with an arbuscular mycorrhizal biofertilizer containing Glomus intraradices

Abstract: The aim of the present study was to determine whether arbuscular mycorrhizal (AM) inoculation with a biofertilizer containing clays as granular carriers, leek root pieces and Glomus intraradices spores could improve alkalinity tolerance of two cucumber genotypes, and to study the changes induced by AM at agronomical and physiological level. A greenhouse experiment was carried out to determine yield, growth, fruit quality, net photosynthesis (ACO2), electrolyte leakage, and mineral composition of two cucumber (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 45 publications
5
28
0
5
Order By: Relevance
“…The increase in root growth and the development of an external mycelium enhanced the nutrient uptake of the tested crops. Our results are in line with those of Rouphael et al and Cardarelli et al , who observed an improvement in nutrient uptake when plants were inoculated with G. intraradices BEG72. The better plant nutritional status due to greater absorption of nutrients in the greenhouse (e.g.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The increase in root growth and the development of an external mycelium enhanced the nutrient uptake of the tested crops. Our results are in line with those of Rouphael et al and Cardarelli et al , who observed an improvement in nutrient uptake when plants were inoculated with G. intraradices BEG72. The better plant nutritional status due to greater absorption of nutrients in the greenhouse (e.g.…”
Section: Discussionsupporting
confidence: 94%
“…The association of AM fungi with plant roots alters plant–soil interactions and enhances plant growth under stressful edaphic conditions . AM fungi have been shown to enhance plant nutrient acquisition (P, N, K), overcome the detrimental effects of salinity and alkalinity, improve drought tolerance through greater effective root area and penetration of the substrate, and activate and excrete various enzymes of infected AM fungi roots and/or hyphae…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CaCO 3 (4 g/l) was added to peat to obtain a pH of 7.0. Prior to sowing, half of the pots were inoculated with R. irregularis (Aegis Irriga, Italpollina SpA., Verona, Italy) carrying 100 spores/ml by mixing 1 m 3 of the substrate with 15 l of inoculum mixture (Rouphael et al 2010). Three pregerminated seeds were planted in each pot and were thinned to one plant per pot after establishment.…”
Section: Plant and Amf Inoculation Proceduresmentioning
confidence: 99%
“…Plants show minor to severe stunting of growth depending on HCO 3 − concentration in the soil solution. Growth of many commercial crops such as bean (Valdez-Aguilar & Reed, 2008;, cucumber (Rouphael et al, 2010), wheat (Yang et al, 2008c), sorghum, maize barley (Alhendawi et al, 1997;Yang et al, 2009), soybean (Rogovska et al ,2009), sunflower (Alcántara et al, 1988Shi & Sheng, 2005), tomato (Bailey & Hammer, 1986;Bialczyk & Lechowsk, 1995;Bialczyk et al, 2004;Navarro et al, 2000), pea (Zribi & Gharsalli, 2002), and rice (Hajiboland et al, 2005;Yang et al, 1994) are reported to be www.intechopen.com considerably affected by HCO 3 − . Toxic concentrations of bicarbonate can diminish leaf area, leaf length and leaf width, consequently shoot biomass is decreased.…”
Section: Effect Of Alkalinity On Plant Growthmentioning
confidence: 99%